USIA MENARCHE, KONSUMSI PANGAN, DAN STATUS GIZI ANAK PEREMPUAN SEKOLAH DASAR DI BOGOR - Sanya Anda Lusiana; Cesilia Meti Dwiriani (Food and Nutrition Society of Indonesia, 2007)
The general objective of this research was to analyze the correlation between nutritional status, food consumption, and first menstruation age (menarche) of female Elementary School children. The research was conducted using cross sectional study design from May to June 2007 in 14 Elementary Schools in Bogor. Sample criteria was: 5 grade student consist of pre menarche and post menarche students. A total of 120 students was chosen by purposive sampling. Spearman Correlation Test shows that there was no correlation between menarche age of mother and menarche age of the sample. Post menarche sample had sufficient energy intake but low iron intake. About 86.7% post menarche sample and 68.3% pre menarche sample had normal nutritional status. Spearman Correlation Test shows that nutritional status (BMI/Age) has negative significant correlation to menarche age (r=-0.062; P<0.05). It means that better nutritional status implied in earlier menarche age.